Coal and Coalbed Methane Co-Extraction Technology Based on the Ground Movement in the Yangquan Coalfield, China - Guozhong Hu; Jialin Xu; Fuxi Zhang; Changchun Zhao; Wei Qin; Yiran Zhu (Energies, 2015)
The Yangquan coalfield is one of the typical highly gassy mining areas in China. However, its coal seams are of lower permeability, which are not conductive to coalbed methane (CBM) drainage. In this study, based on the theory of the ground movement, we analyzed the principle of coal and CBM coextraction in the Yangquan coalfield, and established the technology system of coal and CBM coextraction which was further implemented in the coal and CBM coextraction in the Yangquan coalfield. The coal and CBM coextraction technologies based on the “pressure-relief and permeability-increase” effect caused by the mining overburden movement can optimally ensure the safe and efficient mining and improve the gas drainage rate. A series of developed coal and CBM coextraction technologies for the Yangquan coalfield were mainly characterized by the high-level gas drainage roadway. This reached a maximum gas drainage amount of 270,000 m3/day for single drainage roadway and a pressure-relief gas drainage rate of >90%. Those technologies significantly improved the gas drainage effect safely and efficiently achieving the coal and CBM coextraction.